2019
DOI: 10.29309/tpmj/2019.26.08.3870
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of undergraduate medical students about peer assisted learning.

Abstract: To assess the perceptions of undergraduate medical students about peer assisted learning (PAL). Study Design: Cross sectional study. Setting: Peshawar Medical College. Period: From March 2016 to August 2016. Materials and Methods: A total of 84 students from second year MBBS were included to record the perceptions about peer assisted learning. A total of six topics of urogenital module were selected for PAL session. A validated questionnaire having 17 close ended questions was used to evaluate PAL on Likert-sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 17 publications
(19 reference statements)
1
6
0
Order By: Relevance
“…The interns found PAL as an effective and interesting activity, and they recommended this method to all unit orientation. This is in congruence with other studies where respondents were satisfied with this method and encourage the implementation of this strategy (Usman & Jamil, 2019;Andrew et al, 2016;Cameron et al, 2015; Bahaa, 2015) 8,12,16,17 .…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The interns found PAL as an effective and interesting activity, and they recommended this method to all unit orientation. This is in congruence with other studies where respondents were satisfied with this method and encourage the implementation of this strategy (Usman & Jamil, 2019;Andrew et al, 2016;Cameron et al, 2015; Bahaa, 2015) 8,12,16,17 .…”
Section: Discussionsupporting
confidence: 90%
“…Studies show that PAL increases confidence for tutors as well as tutees. Using PAL also enhances communication and presentation skills (Usman & Jamil, 2019) 8 . In addition, PAL gave tutors the opportunity to reflect on their previous experience, this supports previous study which indicates that taking the responsibility to prepare and deliver a lesson increases deep understanding of the task (Cameron et al, 2015) 16 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the results and discussions on reviewed studies, this study have found that Singh, Scicluna, and Abdolalizadeh all had strongly implied the benefit of peer mentoring program in developing students' communication skills. Supported by previous study with similar result [14]- [17], Singh et al found in their studies that mentors developed improvement in communication skills as a result of mentoring activities, as the previous study [9]. Scicluna et al found that teaching their juniors improved mentors' communication skills.…”
Section: Good Communication Skillsmentioning
confidence: 57%
“…PAL coordinators are skilled leaders, who have the experience of creating session plans. They must have sufficient knowledge and confidence (Usman & Jamil, 2019) to answer both the leaders' and participants' questions during and outside the sessions. They need to be approachable and fair, but also assertive enough to manage the scheme.…”
Section: Pal Coordinatormentioning
confidence: 99%